Primary peritoneal clear cell carcinoma. A case report and literature review - Gloria Peiro; Sandra Silva-Ortega; Cristina Garcia-Espasa; Manuela Sala-Ferichola; Sandra Perez-Vicente; Elena Castellon-Molla; Josefa Marcos-Sanmartin (Elsevier, 2020)
Primary peritoneal malignant tumors are exceptional. Among them, clear cell carcinoma is extremely rare, being only thirteen cases previously reported in the literature since 1990. We report a case of a 48-year-old Caucasian woman who was treated at the University General Hospital of Alicante. She consulted because of progressive abdominal pain over the last seven months, with the initial diagnosis of renal-ureteral colic. Ultrasound and computed tomography of the abdomen and pelvis revealed a 25 × 15 cm, well-defined cystic lesion with papillary projections, centrally located in the abdomen. The radiology report suggested a primary ovarian tumor versus peritoneal implant as the first option. The patient underwent an exploratory laparotomy showing a large cystic mass located in the urinary bladder peritoneum, firmly attached to the mesentery. The entire abdominal tumor was completely excised, and total hysterectomy with bilateral salpingo-oophorectomy and infra-colical omentectomy were performed. The final histological study revealed a new case of primary peritoneal clear cell carcinoma located in the urinary bladder peritoneum, firmly attached to the mesentery. Grossly, it was well-circumscribed and multicystic with papillary growth involving part of the inner wall. Microscopically, it showed tubulocystic and papillary patterns with highly atypical tumor cells. After an extensive immunohistochemical analysis, the most relevant finding was an ARID1A loss that was corroborated by molecular analysis showing an ARID1A deletion. The patient received systemic chemotherapy with carboplatin and paclitaxel protocol (Å ~ 4 cycles). Patient follow-up after the eighth month showed peritoneal implants predominantly in the right diaphragmatic cupule that were histologically confirmed as recurrence. She has just received another six cycles of chemotherapy with carboplatin and paclitaxel. Recognition of primary peritoneal clear cell carcinoma in this uncommon location, and exclude metastasis from the ovary, represents a diagnostic challenge.